Prevailing vitamin D status influences mitochondrial and glycolytic bioenergetics in peripheral blood mononuclear cells obtained from adults - Calton, Emily; Keane, Kevin; Soares, Mario; Rowlands, Jordan; Newsholme, Philip (Elsevier BV, 2016)
© 2016 The Authors. Background Circulating peripheral blood mononuclear cells (PBMCs) are exposed to metabolic and immunological stimuli that influence their functionality. We hypothesized that prevailing vitamin D status [25(OH)D] would modulate the bioenergetic profile of PBMCs derived from humans. Materials and methods 38 participants (16 males, 22 females) ranging in body fat from 14–51% were studied. PBMCs were isolated from whole blood, counted and freshly seeded for bioenergetic analysis using the Seahorse XFe96 flux analyser. Whole body energy metabolism via indirect calorimetry, body composition by dual-energy X-ray absorptiometry, and relevant clinical biochemistry were measured. Data was analysed based on 25(OH)D cut-offs of <50 nmol/L (Group 1, n=12), 50–75 nmol/L (Group 2, n=15) and =75 nmol/L (Group 3, n=11). A multivariate general linear model adjusting for age, fat mass, fat-free mass, parathyroid hormone and insulin sensitivity was used. Results There were significant differences in cellular mitochondrial function between groups. Group 1 had significantly higher basal respiration (p=0.001), non-mitochondrial respiration (p=0.009), ATP production (p=0.001), proton leak (p=0.018), background glycolysis (p=0.023) and glycolytic reserve (p=0.039) relative to either Group 2 or Group 3; the latter two did not differ on any measures. There were no differences in bioenergetic health index (BHI), resting metabolic rates and systemic inflammatory markers between groups. Conclusions Inadequate vitamin D status adversely influenced bioenergetic parameters of PBMCs obtained from adults, in a pattern consistent with increased oxidative metabolism and activation of these cells.